Synthesis of Silica Gel From Rice Husk Ash for Sustainable Air Conditioning Requirements - Syahbardia; Berkah Fajar Tamtomo Kiono; Sonny Handojo Winoto; Mohamad Said Kartono Tony Suryo; Dedi Lazuardi (Advance Sustainable Science Engineering and Technology, 2025)
An increase in air conditioning demand, driven by global warming and the need for comfort, highlights the importance of energy-efficient systems like desiccant cooling. This research explores using rice husk ash (RHA), an agricultural waste product from Indonesia, to synthesize silica gel for these systems. The study involved synthesizing silica gel from RHA through chemical processes and comparing its sorption capacity to commercial silica gel. Two synthesis methods were tested: a direct reaction of water glass with acid compounds and an impregnation process on honeycomb walls. The results indicate that the direct reaction method produces a silica gel with better pore performance. Ultimately, the study found that RHA from West Java, Indonesia, is a viable raw material for desiccant air conditioning, although its sorption capacity is slightly lower than that of commercial silica gel. This offers a valuable use for agricultural waste.